(untitled) (Experimental biology, 2025)
The article presents the results of in vivo studies on the determination of the average LD50 dose and toxicity class of a new drug substance, polyene antibiotic Roseofungin. Roseofungin is a carbonyl-conjugated pentaene that inhibits the growth of trichophytosis, microsporia, favus, candidiasis, cryptococcosis, sporotrichosis, chromomycosis, aspergillosis and other human mycosis pathogens. Acute toxicity of the drug substance Roseofungin was studied by a single oral administration of solutions of the substance Roseofungin in doses of 50 mg/kg; 300 mg/kg; 1000 mg/kg and 2000 mg/kg of animal weight to outbred mice of four experimental groups in the amount of 20 animals, weighing 20 g ± 10%. Biological reactivity and death of animals was not observed in any of the groups during 14 days of observation. After 14 days of observation, the animals were euthanised, autopsied and macroscopied. No pathological changes of internal organs of animals in all studied groups were revealed. ...